RANCANG BANGUN MONITORING SISTEM KEAMANAN LINGKUNGAN MENGGUNAKAN KOMUNIKASI WIRELESS DENGAN TOPOLOGI MESH - Isnanta, Nisantyo Permana; Harianto, Harianto; Triwidyastuti, Yosefine (Journal of Control and Network Systems (JCONES), 2017)
A security system environment will be good if every homes in the neighborhood have a good security system. It will reduce the space for crime in the neighborhood, so that any crimes that arise can be directly detected. Therefore, it is necessary that efforts be made a serious and well coordinated security issues related to the environment.             Environmental security system implemented on Arduino microcontroller module receives data from android application that is sent via Bluetooth serial HC05. Then the data received can be sent to another node serially using XBee wireless module S2. The reading of the condition of the door is done by limit switch sensors taped to the top of the door .Result data limit switches  will be sent to the Arduino microcontroller Mega2560. The  data results in microcontroller can be transmitted to the  XBee module to be implemented in the form of flame LED and buzzer sounds.             In the test results for the implementation of this system , data transmission and reception can success  100%. And examination of  information display on the guardhouse updated from every home success rate was 74, 29%. Keyword: Environmental Security Systems, XBee S2, Bluetooth HC05, Arduino Mega 2560, Arduino UNO, Mesh Networking.